The light of days : the untold story of women resistance fighters in Hitler's ghettos - Batalion, Judith (William Morrow, 2020)
"One of the most important untold stories of World War II. The light of days is a soaring landmark history that brings to light the extraordinary accomplishments of brave Jewish women who helped weaponize Poland's Jewish youth groups to resist the Nazis. Witnesses to the brutal murder of their families and the violent destruction of their communities, a cadre of Jewish women in Poland--some still in their teens--became the nerves of a wide-ranging resistance network that fought the Nazis"--Jacket flap.